THE INFLUENCE OF ABDOMINAL PIGMENTATION ON DESICCATION AND ULTRAVIOLET RESISTANCE IN TWO SPECIES OF DROSOPHILA. (3rd May 2013) - Matute, Daniel R.; Harris, Alexandra
Abstract : Drosophila yakuba and D. santomea are sister species that differ in their levels of abdominal pigmentation; D. yakuba shows heavily pigmented posterior abdominal segments in both sexes, whereas D. santomea lacks dark pigment anywhere on its body. Using naturally collected lines, we demonstrate the existence of altitudinal variation in abdominal pigmentation in D. yakuba but not in D. santomea . We use the variation in pigmentation within D. yakuba and two body‐color mutants in D. yakuba to elucidate selective advantage of differences in pigmentation. Our results indicate that although differences in abdominal pigmentation have no effect on desiccation resistance, lighter pigmentation confers ultraviolet radiation resistance in this pair of species.